Evaluating the impact of a coach development intervention for improving coaching practices in junior football (soccer): The "MASTER" pilot study - Eather, N.; Jones, B.; Miller, A.; Morgan, P. J. (Journal of Sports Sciences, 2020)
The aim of this pilot study was to evaluate the impact of a novel coach development intervention (MASTER) on coaching practices of football coaches. The study involved six coaches (of 10-12 year old) from one representative football club (Australia February-July 2017). The 15-week multi-component intervention included a face-to-face workshop, ongoing mentoring, modelled training sessions, peer assessments and group discussions. MASTER is underpinned by positive coaching and game-based coaching practices and aimed to educate coaches on how to implement and operationalise a number of evidence-based coaching elements. At each of baseline and immediate post-intervention coaches were filmed three times and evaluated using a modified version of the Coach Analysis Intervention System. Using linear mixed model analysis, significant changes were observed for time spent performing playing-form activities [+15.4% (95% CI 6.01-24.79)(t(15) = 3.5, P = 0.003], with significant changes in the type of interventions undertaken and the nature of feedback given to athletes. Program feasibility was examined using measures of recruitment, retention, adherence and satisfaction. Results indicate program feasibility and high coach evaluation ratings. MASTER demonstrated effectiveness for improving coaching practices of football coaches during training sessions. Further large-scale trials will build evidence for the utility of MASTER for guiding coaching practices in football and other sporting codes.